Peningkatan Keterampilan Menulis Menggunakan Huruf Kapital Melalui Strategi Menulis Terbimbing Berbantuan Media Puzzle pada Siswa Kelas II - Anisatul Munawaroh, Dewi; Dewi Koeswanti, Henny (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2024)
This research was conducted to describe the improvement in writing skills for class II students using capital letters by implementing guided writing strategies assisted by puzzle media. This type of research is classroom action research using the Kemmis and Mc model research design. Taggart is carried out in 2 cycles. Each cycle has four stages: planning, implementation, observation, and reflection. The research subjects in class II were 11, including four female and seven male students. Research data was collected through observation and writing tests. The data analysis technique used is percentage analysis. Data analysis was carried out on the results of the writing skills test using capital letters. Based on the implementation of the research, it showed that the percentage of students' completion increased significantly in the pre-cycle by 18%, increased in cycles 1 to 54%, and cycles 2 to 80%. So, the application of guided writing strategies assisted by puzzle media can be said to be successful in improving writing skills using capital letters in class II students